The potential for industrial activity among EU regions: An empirical analysis at the NUTS2 level - Martin Gornig; Axel Werwatz (Humboldt-Universität zu Berlin, DFG Research Unit 2569 FORLand "Agricultural Land Markets - Efficiency and Regulation", 2019)
In the last decade, many parts of the world experienced severe increases in agricultural land prices. This price surge, however, did not take place evenly in space and time. To better understand the spatial and temporal behavior of land prices, we employ a price diffusion model that combines features of market integration models and spatial econometric models. An application of this model to farmland prices in Germany shows that prices on a county-level are cointegrated. Apart from convergence towards a long-run equilibrium, we find that price transmission also proceeds through short-term adjustments caused by neighboring regions.
Keywords: Q24; C23; 330; Agricultural land markets; price diffusion; spatial dependence; ripple effect